DNA packaging orders the membrane of bacteriophage PRD1. - Butcher, S J (1995)
Bacteriophage PRD1 contains a linear dsDNA genome enclosed by a lipid membrane lying within a protein coat. Determination of the structure of the detergent-treated particle to 2 nm by cryo-electron microscopy and three-dimensional reconstruction has defined the position of the major coat protein P3. The coat contains 240 copies of trimeric P3 packed into positions of local 6-fold symmetry on a T = 25 lattice. The three-dimensional structures of the PRD1 virion and a DNA packaging mutant to a resolution of 2.8 nm have revealed specific interactions between the coat and the underlying membrane. The membrane is clearly visible as two leaflets separated by 2 nm and spanned by transmembrane density. The size of the coat does not change upon DNA packaging. Instead, the number of interactions seen between the protein shell and the membrane and the order of the membrane components increase. Thus the membrane of PRD1 plays a role in assembly which is akin to that played by the nucleocapsid in other membrane viruses.